Resorcinol-type phenolic compounds from natural sources inhibut α-MSH induced melanogenesis and UVA-induced DNA damage - Hu, Shuting (The University of Hong Kong (Pokfulam, Hong Kong), 2014)
Sunlight exposure is inevitable to all humans and UV radiation in the sunlight usually causes damages to the skin. Tanning, first appearing when UV injures occur, is a pigmentation process which can be considered as a natural defense mechanism of the organism. Melanin plays an important role in the prevention of the skin from harmful environmental factors such as UV radiation. However, the excess accumulation of melanin causes hyperpigmentation, which is associated with a number of unhealthy conditions including solar lentigines, melasma, freckles and post-inflammatory hyperpigmentation. Therefore, the development of safe and effective hypopigmenting agents is of great importance.